2002
DOI: 10.1007/s00277-002-0488-x
|View full text |Cite
|
Sign up to set email alerts
|

Overview of 321 patients with idiopathic thrombocytopenic purpura

Abstract: In this retrospective study, we evaluated the clinical features and the effects of various treatment modalities on the clinical course in patients diagnosed with idiopathic thrombocytopenic purpura (ITP) at our center between 1984-2000. We retrospectively examined the medical records of 321 (229 females, 92 males) ITP patients. One hundred and seventy-one (53.3%) patients were lost to follow-up. When evaluating the clinical features, all 321 patients were included; however, when the response to treatment modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 6 publications
5
11
0
Order By: Relevance
“…Following splenectomy, 50% of our elderly ITP patients achieved stable response with no immediate adverse effects ( Table 2). This is consistent with the literature, which supports the theory that splenectomy provokes long durable response in elderly ITP patients [10][11][12][13][14][15][16][17][18]. In a previous study, our team demonstrated that age negatively influences the response to splenectomy while correlating to more frequent postoperative complications [9].…”
Section: Discussionsupporting
confidence: 91%
“…Following splenectomy, 50% of our elderly ITP patients achieved stable response with no immediate adverse effects ( Table 2). This is consistent with the literature, which supports the theory that splenectomy provokes long durable response in elderly ITP patients [10][11][12][13][14][15][16][17][18]. In a previous study, our team demonstrated that age negatively influences the response to splenectomy while correlating to more frequent postoperative complications [9].…”
Section: Discussionsupporting
confidence: 91%
“…The remaining 90% patients showed signs of bleeding. This rate was higher than those described in the published literature for the all-age groups, but was similar to that in other series of elderly patients[ 20 , 57 ]. Although severe bleeding events, especially life-threatening ones, are much less common[ 58 59 ], in our research, among five patients who became chronic, three were elderly patients and the one died of cerebral hemorrhage was 67 years of age.…”
Section: Discussionsupporting
confidence: 89%
“…In multivariate analysis, younger age and higher peak post splenectomy platelet counts were significantly associated with a favorable response to splenectomy. 26 In an overview of 321 patients by Pamuk, splenectomy was performed in 76 patients and complete response was obtained in 68.4% of the regularly followed up patients and splenectomy seemed to be effective in patients unresponsive to steroids. 26 With the changing concepts about the role of staging laparotomy in Hodgkin's Lymphoma, from its introduction, staging laparotomy was intended only for patients in whom radiation therapy potentially could be the sole therapeutic modality.…”
Section: Resultsmentioning
confidence: 99%
“…26 In an overview of 321 patients by Pamuk, splenectomy was performed in 76 patients and complete response was obtained in 68.4% of the regularly followed up patients and splenectomy seemed to be effective in patients unresponsive to steroids. 26 With the changing concepts about the role of staging laparotomy in Hodgkin's Lymphoma, from its introduction, staging laparotomy was intended only for patients in whom radiation therapy potentially could be the sole therapeutic modality. Surgical staging allows treatment to be chosen with specific knowledge regarding the extent of disease but has an associated morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%